FEATURES OF THE TRANSLATION OF FRENCH COLLOQUIAL VOCABULARY (Academia Science Repository, 2023)
The article raises the problems of translation of French language popular science texts; describes the main difficulties encountered in translation; studies the peculiarities of vocabulary translation; highlights the main forms of popular science text and gives their definitions; the text is considered as the basic unit of the language.